New Technologies and Innovative Solutions in the Development of Multimedia Corpus of Mezen Robinsons Texts - Shvetsova, Tatiana V.; Shakhova, Veronika E.; Dulova, Svetlana A. (HighTech and Innovation Journal, 2023)
Objective: New Technologies and Innovative Solutions in creating a multimedia corpus of texts about the "Mezen Robinsons" aims to preserve the memory of an event that occurred in the 18th century and to study the history of Spitsbergen development. This article presents a multimedia corpus of Russian-language texts about the "Mezen Robinsons" written in 1766–2022. Observations show that the history of the survival of the Mezen hunters on Edge Island in 1743–1749 has repeatedly attracted the attention of specialists from various fields of knowledge: historians, archaeologists, publicists, professional writers, translators, etc. The corpus unites texts, audio, video, and multimedia resources. Methods: continuous sampling was used to collect the material; when analyzing and describing the data, we applied a descriptive method, a biographical method of studying literature, statistical data processing, philological analysis, observation, assessment, and corpus modeling methods. Findings: the methodology and technology of building an independent multimedia corpus, its architecture, and its design are described. Novelty: the multimedia corpus is a contribution to the development of a new approach to studying the subjectology of Russian literature. Practical significance:the findings can become the basis for studying the biographies and creativity of various authors who built their works on the plot of the Mezen industrialists and for further comparison of various interpretations of one event from the history of the development of the Arctic. Doi:10.28991/HIJ-2023-04-01-07 Full Text: PDF